Mycorrhizal status of Phlebopus bruchii (Boletaceae): Does it form ectomycorrhizas with Fagara coco (Rutaceae)? - Nouhra, Eduardo Ramon (2008)
Fagara coco(Gill.) Engl, a native tree in the mountains of Central Argentina generally grows associated with Phlebopus bruchii (Speg.) Heineman & Rammeloo. The association with this edible bolete has been considered an ectomycorrhizal symbiosis. To test the hypothesis of their co-occurrence as mutualistic partners, we studied mycorrhizal colonization in roots from natural stands and roots inoculated with spores of P. bruchii in a greenhouse and pure culture experiments. No ectomycorrhizal (ECM) colonization was detected. Instead, roots collected from the field were colonized by arbuscular mycorrhizal (AM) fungi showing dual infection of Arum and Paris type morphologies. The percentage of AM mycorrhizal colonization varied among seasons, being higher in autumn. Spores of ten Glomalean taxa were isolated from F. coco rhizosphere. Based on the results achieved and previous data available, we suspect that the genus Phlebopus is an exception to the mycorrhizal habit of most Boletales.